Subclinical features of atherosclerotic remodeling of arteries in patients with rheumatoid arthritis - I. M. Fushtei; O. V. Tkachenko; S. L. Podsevakhina; O. I. Palamarchuk (Zaporozhye State Medical University, 2019)
The aim of the research - to study the structural-functional state of artery walls in patients with rheumatoid arthritis depending of disease duration, seropositivity for rheumatoid factor/ cyclic citrullinated peptide antibodies, disease activity. Materials and methods. 82 patients with rheumatoid arthritis were investigated: 19 men (23.1 %) and 63 women (76.9 %), the average age of whom was (37.6 ± 5.1) years old. The control group consisted of 30 apparently healthy persons. In all the patients measurements of diameter and thickness of intima-media complex of common carotid arteries were carried out, the stiffness index was calculated. Results. 47.5 % (n = 39) of patients had rheumatoid arthritis with the present illness duration less than 3 years, in 47.5 % of patients (n = 39) the duration of rheumatoid arthritis was more than 3 years. In 48 (58.5 %) of patients rheumatoid factor/cyclic citrullinated peptide antibodies were present - seropositive variant of rheumatoid arthritis, in 34 (41.5 %) patients - rheumatoid factor/cyclic citrullinated peptide antibodies seronegative variant of the disease. Within all investigated patients with rheumatoid arthritis the highest rates of intima-media thickness complex of common carotid arteries were detected in patients with longer-term (more than 3 years) present illness rheumatoid factor/cyclic citrullinated peptide antibodies of seropositive rheumatoid arthritis; in patients of this group higher stiffness index of common carotid arteries was also detected that characterizes the local (carotid) rigidity of artery wall. Correlation analysis showed the existence of direct relationship between DAS28 and intima-media complex of common carotid arteries, the duration of rheumatoid arthritis and stiffness index of intima-media complex of common carotid arteries, and also between their size and the level of rheumatoid factor, cyclic citrullinated peptide antibodies, which shows the substantial contribution of activity and duration of autoimmune inflammation course in rheumatoid arthritis to changes of common carotid arteries architectonics. Conclusions. The data obtained demonstrate the existence of subclinical lesion of common carotid arteries in patients with rheumatoid arthritis and absence of cardiovascular diseases, more significant in long-term course (more than 3 years) of seropositive for rheumatoid factor/ cyclic citrullinated peptide antibodies disease variant.